Influence of Different Intensities of Tillage on Physiological Characteristics and Productivity of Crop-Rotation Plants - Daiva Janusauskaite; Grazina Kadziene (Plants, 2022)
The aim of this study was to evaluate the effect of different intensities of tillage on the physiological characteristics and productivity of plants in crop rotation. Five tillage practices (DP—deep ploughing (22–24 cm); SP—shallow ploughing (16–18 cm); SH—shallow harrowing (8–10 cm); DH—deep harrowing (14–16 cm); and DD—direct drilling) were investigated in a long-term experiment in Dotnuva. The crop rotation was as follows: winter oilseed rape → spring wheat → spring barley → field pea → winter wheat. The simplification of conventional tillage negatively affected the photosynthetic indices of the majority of the crop rotation plants. The most favorable conditions for the photosynthetic processes in the plants were identified in the deep-ploughing treatment. The photochemical activity was negatively influenced and leaf senescence was accelerated under direct drilling. Direct drilling significantly decreased the grain yield of winter oilseed rape, spring wheat, and spring barley by 10.5%, 12.8%, and 17.2%, respectively, compared to deep ploughing. The grain yield of winter wheat was similar under deep ploughing and direct drilling; conversely, under shallow ploughing, shallow harrowing, and deep harrowing, the yield tended to decrease compared to deep ploughing.